ENT600: Nori Norish Dpa / Intan Najeha Mohd Hisham … [et al.] - Mohd Hisham, Intan Najeha; Zainal Ariff, Nor Zaijanatul; Shahrom, Nur Adilah; Mohamad Zahir, Nur Syifa; Roslan, Rosmariani (2018)
Nori Norish Spa is specialised in facial treatment. They also provide other services such as body treatment, sell skin care product, health supplement and scarf. The company have been operated for 12 years' and very experience on facial treatment. However, they did not provide full body treatment services even though there are high request from the customers nearby area. The services are also quite expensive and not affordable for low income community. Thus, there is a few recommendations in order to solve these problems. One of them is by enhancing the marketing strategies social media approaches. The supervisor should involve more actively in internet marketing by gathering more information on Search Engine Online (SEO). Consumer Trend Canvas also helps the company in analysing insights about the consumer trends and transform them into innovation and business opportunities.